Transformational Leadership and Workplace Spirituality: A Structural Model of Team Effectiveness - Nandana Prabhu, K. P.; Rodrigues, Lewlyn L. R.; Pai, Yogesh (Prabandhan: Indian Journal of Management, 2019)
The purpose of this research endeavor was to evaluate the effects of team transformational leadership and workplace spirituality on team effectiveness. This research sought to determine the impact of team culture, embedded in team transformational leadership, on team effectiveness. Further, it evaluated the comparative effects of the constructs of team interaction process and workplace spirituality on creation of process effects that lead to team effectiveness. This study adopted the partial least squares structural equation modeling (PLS-SEM) approach to test the hypotheses relating to the relationship among the exogenous constructs such as team transformational leadership, team interaction process, and workplace spirituality with the endogenous construct, that is, team effectiveness. This research investigated the relationship among these constructs on a sample of 130 teams of IT organizations. Situating team transformational leadership as a cultural construct in the team effectiveness research discourse ; the importance of internalized intrinsic motivation resulting from workplace spirituality in influencing team effectiveness ; empirical validation of the status of transformational leadership as a precursor to workplace spirituality ; the need to combine 'outside-in' and 'inside-out' approaches to team processes so as to increase the degree of team effectiveness ; performance - determining influence of team processes that outshines the performance-determining impact of transformational leadership were the specific contributions of this study to team effectiveness research. The need to cultivate team culture embedded in transformational leadership behaviors, team - level necessity to pay attention to the 'spiritual' side of team members, situating team leadership behaviors vis-Ã -vis member interaction behaviors in the context of team effectiveness were the managerial implications of this research.